Osteoclast-like activity of U937 cells, peripheral blood mononuclear cells, and periodontal ligament fibroblasts subjected to mechanical stress by centrifugal force - Carlos Guerrero Fonseca; Pedro Moreno Beltrán; Angie Bedoya Rodríguez; Bibiana Pazos Valencia; Juan Sebastián Bedoya Trujillo; Orlando Acosta (Universitas Scientiarum)
Several in vitro models have investigated the consequences of mechanical stimuli on osteoclasts (OCs). However, the mechanisms whereby mechanical forces trigger osteoclast responses remain poorly understood, and the generation of reactive oxygen species (ROS) and their relationship with bone resorption in OCs under the influence of mechanical forces require investigation. The present work examined the role of centrifugal force application on ROS production and its effect on osteoclast activity and differentiation. Human U937 macrophage cells, peripheral blood mononuclear cells (PBMCs), and periodontal ligament (PDL) fibroblasts treated with polyethylene glycol (PEG) or N-acetylcysteine (NAC) were subject to centrifugal force. Osteoclast markers such as tartrate-resistant acid phosphatase (TRAP) and bone resorption activities were measured. ROS levels and actin ring formation were determined. Also, U937 cell responses to centrifugal force and PEG-induced fusion were studied. Individual cells subjected to centrifugal exertion increased their ROS levels, formed actin-like rings, revealed TRAP expression and bone resorption activities, and expressed typical osteoclast markers. Control PEG-fused U937 cells also showed these effects, and cell treatment with NAC stopped all these responses. Centrifugal force, as well as PEG-induced cell fusion, can promote osteoclast-like features, including oxidative stress. The present experimental model allowed us to understand the mechanisms underlying the osteoclast differentiation associated with ROS production stimulated by mechanical compressive force, where NAC can contribute to reducing this oxidative stress condition.